2011
DOI: 10.1161/strokeaha.111.619734
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Malignant Middle Cerebral Artery Infarction Using Computed Tomography-Based Intracranial Volume Reserve Measurements

Abstract: Background and Purpose-Early decompressive surgery in patients with malignant middle cerebral artery (MCA) infarction improves outcome. Elevation of intracranial pressure depends on both the space occupying brain edema and the intracranial volume reserve (cerebrospinal fluid [CSF]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 25 publications
6
88
2
1
Order By: Relevance
“…In other articles, clinical deterioration was quantified and also considered in the definition of prominent space-occupying edema or malignant MCA infarction. 12,14,30 It is, however, unlikely that patients with prominent space-occupying edema or substantial hemorrhage were missed because additional CT scans were always obtained in case of clinical deterioration during the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In other articles, clinical deterioration was quantified and also considered in the definition of prominent space-occupying edema or malignant MCA infarction. 12,14,30 It is, however, unlikely that patients with prominent space-occupying edema or substantial hemorrhage were missed because additional CT scans were always obtained in case of clinical deterioration during the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…At least a brain computed tomography (CT) scan must be performed to distinguish between ischemic and hemorrhagic stroke. 5 The Committee suggests a one-stop diagnostic procedure, including a CT perfusion scan when indicated as has recently been reported, 30 and a contrast medium-based CT angiography, including cervical arteries 31,32 when appropriate and available.…”
Section: Early Diagnostic Investigationsmentioning
confidence: 99%
“…The following factors were associated with unfavorable outcome: age, NIH Stroke Scale score for 1 added point on admission, stroke due to atherosclerosis, hemorrhagic transformation of the ischemic lesion, and hyperdense MCA and/or ICA (OR 2.0, 95% CI 1.0-4.0). Recent study (Minnerup et al, 2011), enrolling 52 ischemic stroke patients with carotid-T or MCA main stem occlusion and ischemia (reduced cerebral blood volume) on perfusion CT performed on admission, showed that 26 (50%) of them developed malignant MCA infarction. Two subgroups were separated according to the development of malignant MCA infarction defined by clinical signs of herniation.…”
Section: When We Should Perform a Decompressive Hemicraniectomy?mentioning
confidence: 99%
“…It is estimated that about 10% to 20% of the patients with infarction in the territory of the middle cerebral artery (MCA) or of the internal carotid artery (ICA) develop hemispheric cerebral edema/swelling, presenting signs of uncal and cingulate herniations and neurological deterioration (Paciaroni et al, 2011;Minnerup et al, 2011;Thomalla et al, 2010;Paciaroni et al, 2011). Clinical deterioration of patients with massive MCA infarction (with or without additional involvement of anterior cerebral artery or posterior cerebral artery) is the result of brain edema, which peaks on days 3 to 5, followed afterwards by progressive edema reduction within the following two weeks (Shaw et al, 1959;Merenda & DeGeorgia, 2010;Ng & Nimmannitya, 1970).…”
Section: Introductionmentioning
confidence: 99%